2009
DOI: 10.1007/s11270-009-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Method for Fourier Transform Infrared (FTIR) Spectroscopic Determination of Soil Nitrate Using Derivative Analysis and Sample Treatments

Abstract: This study aimed at examining effective sample treatments and spectral processing for an alternate method of soil nitrate determination using the attenuated total reflectance (ATR) of Fourier transform infrared (FTIR) spectroscopy. Prior to FTIR measurements, soil samples were prepared as paste to enhance adhesion between the ATR crystal and sample. The similar nitrate peak heights of soil pastes and their supernatants indicated that the nitrate in the liquid portion of the soil paste mainly responded to the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Opvallend is dat bepaalde niet-destructieve spectroscopiemethoden, die bij biochar en bodem (Jahn et al, 2006;Linker et al, 2006;Choe et al, 2010) zijn getest, zoals PAS 1 , DRIFTS, ATR-FTIR en Raman, niet bij dierlijke mest zijn getoetst. Reviews over toepassingen van non-destructieve technieken noemen veel toepassingen voor bodem maar nauwelijks voor mest (e.g., Gredilla et al, 2016).…”
Section: Tabel 36 Verklaarde Variantie (R 2 ) En Rpd Bij De Validatiunclassified
“…Opvallend is dat bepaalde niet-destructieve spectroscopiemethoden, die bij biochar en bodem (Jahn et al, 2006;Linker et al, 2006;Choe et al, 2010) zijn getest, zoals PAS 1 , DRIFTS, ATR-FTIR en Raman, niet bij dierlijke mest zijn getoetst. Reviews over toepassingen van non-destructieve technieken noemen veel toepassingen voor bodem maar nauwelijks voor mest (e.g., Gredilla et al, 2016).…”
Section: Tabel 36 Verklaarde Variantie (R 2 ) En Rpd Bij De Validatiunclassified
“…All spectra were recorded between 4,000 and 500 cm⁻¹ on a Bruker ALPHA FTIR Spectrometer in transmission mode. FTIR spectra interpretation was enhanced by using baseline correction and normalisation, as well as resolution enhancements including self-deconvolution (Choe et al 2010;Griffiths & De Haseth 2007;Mariey et al 2001;Naumann et al 1991). Self-deconvolution was performed on each spectrum by manually selecting the Lorentzian function and then reducing FWHH (full width of the peak at half-height) while increasing noise (Griffiths and De Haseth 2007).…”
Section: Microbial Influenced Corrosionmentioning
confidence: 99%
“…By comparing the nitrate peak intensity of soil pastes and their supernatant, it was shown that the nitrate dissolved in soil solution of the paste mainly responded to the FTIR signal. The results obtained are useful for the monitoring of nutrients in soils (Choe et al 2010). …”
mentioning
confidence: 93%